Kearifan Lokal dalam Tarian Serampang Dua Belas di Etnik Melayu: Pendekatan Antropolinguistik - Syafhira, Zhihand; Mayasari, Mayasari; Hidayati, Hidayati; Anayati, Wan; Lubis, Ilham Sahdi (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2024)
Serampang Dua Belas was the characteristic dance of Malay Deli in North Sumatera. This study was aimed at describing and revealing the local wisdom in Serampang Dua Belas dance. This study used the qualitative method. The researcher traced various journals related to the context theory of anthropolinguistics and semiotics use in language for study of its substance. The source of the data in this study was obtained from the twelve movements contained in the Serampang Dua Belas dance. The data was obtained from the record archives of Serampang Dua Belas dance at Istana Maimoon. In analyzing the data, qualitative analysis method was applied based on theory proposed Bogdan and Taylor. The result of the study showed that there were eleventh movements in Serampang Dua Belas dance which every step had its own meaning telling the story about the process of meeting a soul mate right up to the marriage. The meanings of each step were the first love, crush on, falling in love, crazy in love, the sign of love, love in return, looking for the truth, persisting the feeling, giving the answer, proposing, the bride meeting and the marriage.